Tipe-Tipe Kesalahan Konkordansi Gramatikal Sintaksis pada Frasa Bahasa Arab - Supardi, Supardi; Hadi, Syamsul; Poedjosoedarmo, Soepomo; Suhandano, Suhandano (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This research examines concordance errors in grammatical syntax found in Arabic phrases conducted as a case study on the written texts produced by Arabic of IAIN Salatiga’s students. The qualitative approach is used to identify the types of errors. The sources of data in this study arethe students’ thesis proposals, IndonesianArabic translations, and Arabic-free compositions. The analytical method used is error analysis. The study found 19 types of errors which comprise of four phrase structures, namely the head-modifiers, modifier-head, head-head, and the head-apposition in gender, number, and definiteness categories.